The Lack of Dopamine Transporter Is Associated With Conditional Associative Learning Impairments and Striatal Proteomic Changes - Savchenko, Artem; Müller, Carina; Lubec, Jana; Leo, Damiana; Korz, Volker; Afjehi-Sadat, Leila; Malikovic, Jovana; Sialana, Fernando J.; Lubec, Gert; Sukhanov, Ilya (Frontiers in Psychiatry, 2022)
Dopamine (DA) is critically involved in different functions of the central nervous system (CNS) including control of voluntary movement, affect, reward, sleep, and cognition. One of the key components of DA neurotransmission is DA reuptake by the DA transporter (DAT), ensuring rapid clearance of DA from the synaptic cleft. Thus, lack of DAT leads to persistent high extracellular DA levels. While there is strong evidence for a role of striatal dopaminergic activity in learning and memory processes, little is known about the contribution of DAT deficiency to conditional learning impairments and underlying molecular processes. DAT-knockout (DAT-KO) rats were tested in a set of behavioural experiments evaluating conditional associative learning, which requires unaltered striatal function. In parallel large-scale proteomic analysis of the striatum was performed to identify molecular factors probably underlying behavioural patterns. DAT-KO rats were incapable to acquire a new operant skill in Pavlovian/instrumental autoshaping, although conditional stimulus – unconditional stimulus (CS-US) association seems to be unaffected. These findings suggest that DAT directly or indirectly contributes to reduction of transference of incentive salience from the reward to the CS. We propose, that specific impairment of conditional learning might be caused by molecular adaptations to the hyperdopaminergic state, presumably by dopamine receptor 1 (DRD1) hypofunction, as proposed by proteomic analysis. Whether DRD1 downregulation can cause cognitive deficits in the hyperdopaminergic state is the subject of discussion and further studies are warranted to answer this question. This study may be useful for the interpretation of previous and the design of future studies in the dopamine domain.